ECE Educator Training: How to Develop Literacy and Environment Education for Children? - Chandrawati, Titi; Aisyah, Siti (Jurnal Pendidikan Usia Dini, 2022)
Loving the environment is a character that must be instilled in children from an early age. This study aims to describe how efforts to instil love for the environment in preschool. This research uses a collaboration action research method with the intervention of providing information and motivation about the importance of environmental education for ECE educators. The participants were the ECE community represented by eleven ECE teachers in the Tangerang, Sawangan Bogor, Medan, and Batam areas. Data collection was carried out by focus group discussions and interviews as well as the delivery of information related to learning and environmental literacy for children through online meetings. Content analysis was used to interpret the data in this study. The findings of this study indicate that the provision of information and motivation to eleven ECE teachers can make the eleven teachers form the spirit and knowledge of teachers to develop learning and teaching environmental literacy in early childhood classes. The teachers are also trying to green the school environment by planting trees and making various learning activities with the children to get to know and love the environment better. Keywords: ECE educators training, environmental literacy, environmental education References: Bryman, A. (2021). Social Research Methods. Oxford University Press. https://books.google.co.id/books?id=kDZwzgEACAAJ Burdette, H. L., & Whitaker, R. C. (2005). Resurrecting Free Play in Young Children: Looking Beyond Fitness and Fatness to Attention, Affiliation, and Affect. Archives of Pediatrics & Adolescent Medicine, 159(1), 46–50. https://doi.org/10.1001/archpedi.159.1.46 Chu, H., Lee, E. A., Ryung Ko, H., Hee Shin, D., Nam Lee, M., Mee Min, B., & Hee Kang, K. (2007). Korean Year 3 Children’s Environmental Literacy: A prerequisite for a Korean environmental education curriculum. International Journal of Science Education, 29(6), 731–746. https://doi.org/10.1080/09500690600823532 Corraliza, J., Universidad Autónoma de Madrid., Collado, S., & Universidad de Zaragoza. (2019). Ecological Awareness and Children’s Environmental Experience. Papeles Del Psicólogo - Psychologist Papers, 40(2). https://doi.org/10.23923/pap.psicol2019.2896 Dada, D. O., Eames, C., & Calder, N. (2017). Impact of Environmental Education on Beginning Preservice Teachers’ Environmental Literacy. Australian Journal of Environmental Education, 33(3), 201–222. Cambridge Core. https://doi.org/10.1017/aee.2017.27 Denzin, N. K., & Lincoln, Y. S. (2012). Collecting and Interpreting Qualitative Materials. SAGE Publications. https://books.google.me/books?id=5Z8gAQAAQBAJ Disinger, J. F., & Roth, C. E. (1992). Environmental education research news. Environmentalist, 12(3), 165–168. https://doi.org/10.1007/BF01267599 Ernst, J., & Burcak, F. (2019). Young Children’s Contributions to Sustainability: The Influence of Nature Play on Curiosity, Executive Function Skills, Creative Thinking, and Resilience. Sustainability, 11(15). https://doi.org/10.3390/su11154212 Eugenio-Gozalbo, M., Aragón, L., & Ortega-Cubero, I. (2020). Gardens as Science Learning Contexts Across Educational Stages: Learning Assessment Based on Students’ Graphic Representations. Frontiers in Psychology, 11. https://www.frontiersin.org/articles/10.3389/fpsyg.2020.02226 Evans, G. W., Otto, S., & Kaiser, F. G. (2018). Childhood Origins of Young Adult Environmental Behavior. Psychological Science, 29(5), 679–687. https://doi.org/10.1177/0956797617741894 Ewert, A., Place, G., & Sibthorp, Ji. (2005). Early-Life Outdoor Experiences and an Individual’s Environmental Attitudes. Leisure Sciences, 27(3), 225–239. https://doi.org/10.1080/01490400590930853 Friedman, S., Masterson, M. L., Wright, B. L., Bredekamp, S., & Willer, B. (2021). Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth Through Age 8, Fourth Edition (Fully Revised and Updated). National Association for the Education of Young Children. https://books.google.co.id/books?id=Kb-vzQEACAAJ Gifford, R., & Nilsson, A. (2014). Personal and social factors that influence pro-environmental concern and behaviour: A review. International Journal of Psychology, 49(3), 141–157. https://doi.org/10.1002/ijop.12034 Jørgensen, K.-A. (2016). Bringing the jellyfish home: Environmental consciousness and ‘sense of wonder’ in young children’s encounters with natural landscapes and places. Environmental Education Research, 22(8), 1139–1157. https://doi.org/10.1080/13504622.2015.1068277 Kaiser, F. G., Brügger, A., Hartig, T., Bogner, F. X., & Gutscher, H. (2014). Appreciation of nature and appreciation of environmental protection: How stable are these attitudes and which comes first? European Review of Applied Psychology-Revue Europeenne De Psychologie Appliquee, 64, 269–277. Kaya, V., & Elster, D. (2019). A Critical Consideration of Environmental Literacy: Concepts, Contexts, and Competencies. Sustainability, 11(6), 1581. https://doi.org/10.3390/su11061581 Kidman, G., & Casinader, N. (2019). Developing Teachers’ Environmental Literacy through Inquiry-based Practices. EURASIA Journal of Mathematics, Science and Technology Education, 15(6). https://doi.org/10.29333/ejmste/103065 Kim, G., Vaswani, R. T., Kang, W., Nam, M., & Lee, D. (2017). Enhancing Ecoliteracy through Traditional Ecological Knowledge in Proverbs. Sustainability, 9(7). https://doi.org/10.3390/su9071182 Larimore, R. (2016). Defining Nature-Based Preschools. The International Journal of Early Childhood Environmental Education, 4(1), 5. Lincoln, Y. S., Guba, E. G., & Publishing, S. (1985). Naturalistic Inquiry. SAGE Publications. https://books.google.co.id/books?id=2oA9aWlNeooC López-Alcarria, A., Gutiérrez-Pérez, J., & Poza-Vilches, F. (2014). Preschool Education Professionals as Mediators of Environmental Health Education. 6th International Conference on Intercultural Education “Education and Health: From a Transcultural Perspective", 132, 639–646. https://doi.org/10.1016/j.sbspro.2014.04.366 Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (Third edition). SAGE Publications, Inc. Mills, G. E. (2011). Action Research: A Guide for the Teacher Researcher. Pearson. https://books.google.co.id/books?id=-d1XAAAAYAAJ Olgan, R., & Kahri̇Man-Öztürk, D. (2011). An Investigation in the Playgrounds of Public and Private Preschools in Ankara. Education and Science, 36(161), 13. Otto, S., Evans, G. W., Moon, M. J., & Kaiser, F. G. (2019). The development of children’s environmental attitude and behavior. Global Environmental Change, 58, 101947. https://doi.org/10.1016/j.gloenvcha.2019.101947 Otto, S., Kaiser, F. G., & Arnold, O. (2014). The Critical Challenge of Climate Change for Psychology. European Psychologist, 19(2), 96–106. https://doi.org/10.1027/1016-9040/a000182 Pe’er, S., Goldman, D., & Yavetz, B. (2007). Environmental Literacy in Teacher Training: Attitudes, Knowledge, and Environmental Behavior of Beginning Students. The Journal of Environmental Education, 39(1), 45–59. https://doi.org/10.3200/JOEE.39.1.45-59 Phillipson-Mower, T., & Adams, A. D. (2010). Environmental Education Service-Learning in Science Teacher Education. In A. M. Bodzin, B. Shiner Klein, & S. Weaver (Eds.), The Inclusion of Environmental Education in Science Teacher Education (pp. 65–79). Springer Netherlands. https://doi.org/10.1007/978-90-481-9222-9_5 Rosa, C. D., Profice, C. C., & Collado, S. (2018). Nature Experiences and Adults’ Self-Reported Pro-environmental Behaviors: The Role of Connectedness to Nature and Childhood Nature Experiences. Frontiers in Psychology, 9. https://www.frontiersin.org/articles/10.3389/fpsyg.2018.01055 Roth, C. E. (1992). Environmental Literacy: Its Roots, Evolution and Directions in the 1990s. ERIC/CSMEE Publications. https://books.google.co.id/books?id=8ZA6HQAACAAJ Schutte, A. R., Torquati, J. C., & Beattie, H. L. (2017). Impact of Urban Nature on Executive Functioning in Early and Middle Childhood. Environment and Behavior, 49(1), 3–30. https://doi.org/10.1177/0013916515603095 Shallcross, T., O’Loan, K., & Hui, D. (2000). Developing a School Focused Approach to Continuing Professional Development in Sustainability Education. Environmental Education Research, 6(4), 363–382. https://doi.org/10.1080/713664694 Spano, G., D’Este, M., Giannico, V., Carrus, G., Elia, M., Lafortezza, R., Panno, A., & Sanesi, G. (2020). Are Community Gardening and Horticultural Interventions Beneficial for Psychosocial Well-Being? A Meta-Analysis. International Journal of Environmental Research and Public Health, 17(10). https://doi.org/10.3390/ijerph17103584 Ulrich Müller, Viviene A. Temple, Beverly Smith, Kimberly Kerns, Kayla Ten Eycke, Jeff Crane, & John Sheehan. (2017). Effects of Nature Kindergarten Attendance on Children’s Functioning. Children, Youth and Environments, 27(2), 47–69. JSTOR. https://doi.org/10.7721/chilyoutenvi.27.2.0047 Veisi, H., Lacy, M., Mafakheri, S., & Razaghi, F. (2019). Assessing environmental literacy of university students: A case study of Shahid Beheshti University in Iran. Applied Environmental Education & Communication, 18(1), 25–42. https://doi.org/10.1080/1533015X.2018.1431163 Wals, A. E. J., & Benavot, A. (2017). Can we meet the sustainability challenges? The role of education and lifelong learning. European Journal of Education, 52(4), 404–413. https://doi.org/10.1111/ejed.12250 Wilson, R. A. (1996). Environmental Education Programs for Preschool Children. The Journal of Environmental Education, 27(4), 28–33. https://doi.org/10.1080/00958964.1996.9941473